Paraoxanase 1 Deletion Leads to Increased Cardiac Remodeling and Cardiac Fibrosis in a Dahl Salt-Sensitive Rat Model of Chronic Kidney Disease - Soehnlen, Sophia (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF To see the formatted meeting abstract.